Fragility index of block tailed vectors - Ferreira, Helena (2012)
Financial crises are a recurrent phenomenon with important effects on the real economy. The financial system is inherently fragile and it is therefore of great importance to be able to measure and characterize its systemic stability. Multivariate extreme value theory provide us such a framework through the fragility index (Geluk et al., 2007; Falk and Tichy, to appear-a, to appear-b). Here we generalize this concept and contribute to the modeling of the stability of a stochastic system divided into blocks. We will find several relations with well-known tail dependence measures in the literature, which will provide us immediate estimators. We end with an application to financial data.